Formal Housing Sector Reform in Neoliberal Nigeria (International Journal of Built Environment and Sustainability, 2016)
In the past two decades, Nigeria has deployed neoliberal principles in the provision of formal housing. This approach was adopted on the assumption that the implementation of enabling reforms would enhance the role of the private sector and equally promote the development of a formal housing system in Nigeria. This has not occurred; the neoliberal housing approach has brought fewer results than the reform promised. The study therefore aims to explore the agency and actions of Nigerian authorities in response to this neoliberal agenda. To achieve this aim, the following objectives are pursued: The first objective analyses why neoliberalism failed to effectively change the housing market in Nigeria; the second examines the impact of neoliberal restructuring process on housing provision in Nigeria; and the last analyses the success of legislative reform that were carried to support housing provision under Nigeria’s neoliberalism. To achieve these objectives, the paper adopts a documentary method and in accordance with this, a wide range of documentary evidence was collected for a content analysis. The findings of the analysis suggest that economic recession, political instability and changing ideological stances of successive governments affected the consistency of neoliberal reforms. Furthermore, the reforms implemented were seen to be progressive but the events occurred rather slowly, haphazardly and uncoordinated. A time lag is also observed in the reform processes and the sequence of events shows a lack of consideration of the interdependency of legislation and action. This policy review concludes that the neoliberal approach has the potential to improve the delivery of formal housing; however the authorities need to be consistent with the reforms while at the same time aligning legislation and action.